Experimental Assessment of Microbial Fuel Cells for Treatment and Nutrient Recovery from Different Wastewaters - Abdalla, Hadeer (2022)
A Master of Science thesis in Civil Engineering by Hadeer Abdalla entitled, “Experimental Assessment of Microbial Fuel Cells for Treatment and Nutrient Recovery from Different Wastewaters”, submitted in May 2022. Thesis advisor is Dr. Kazi Fattah and thesis co-advisor is Dr. Mohamed Abdallah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).